Resolving the Variscan evolution of the Moldanubian sector of the Bohemian Massif: the significance of the Bavarian and the Moravo-Moldanubian tectonometamorphic phases - Finger,F.; Gerdes,A.; Janousek,V.; Rene,M.; Riegler,G. (Journal of Geosciences, 2007)
The Variscan evolution of the Moldanubian sector in the Bohemian Massif consists of at least two distinct tectonometamorphic phases: the Moravo-Moldanubian Phase (345-330 Ma) and the Bavarian Phase (330-315 Ma). The Moravo- Moldanubian Phase involved the overthrusting of the Moldanubian over the Moravian Zone, a process which may have followed the subduction of an intervening oceanic domain (a part of the Rheiic Ocean) beneath a Moldanubian (Armorican) active continental margin. The Moravo-Moldanubian Phase also involved the exhumation of the HP-HT rocks of the Gfohl Unit into the Moldanubian middle crust, represented by the Monotonous and Variegated series. The tectonic emplacement of the HP-HT rocks was accompanied by intrusions of distinct magnesio-potassic granitoid melts (the 335-338 Ma old Durbachite plutons), which contain components from a strongly enriched lithospheric mantle source. Two parallel belts of HP-HT rocks associated with Durbachite intrusions can be distinguished, a western one at the Tepla-Barrandian and an eastern one close to the Moravian boundary. The combined occurrence of Durbachite plutons and HP rocks would be difficult to understand in terms of the previous tectonic models, in which the Gfohl Unit was viewed as a large flat nappe on top of the Moldanubian Zone. In recent studies it has been suggested that Saxothuringian crust was subducted eastwards under the Moldanubian Zone during the Early Carboniferous. We discuss here an alternative tectonic scenario, in which the south-eastern Bohemian Massif is tentatively interpreted as an accretionary wedge successively underplated by material of a Gfohl and a Moravian terrane. It is suggested that parts of the HP-HT rocks of the Gfohl Terrane were exhumed along the Moravian-Moldanubian plate contact, while earlier subducted portions were steeply uplifted close to the Tepla-Barrandian block, which may have functioned as a rigid backstop of the accretionary wedge. Final stages of the Moravo-Moldanubian Phase were characterised by a strong LP-HT regional metamorphism at c. 335-340 Ma, which may be an expression of increased mantle heat flow after slab break-off, and is seen mainly in the Ostrong Unit along the central axis of the Moravo-Moldanubian Fold Belt. As indicated from palaeomagnetic data, the (already established) Moravo-Moldanubian Fold Belt has then (around 330 Ma) rotated by about 90° clockwise, while the palaeogeographic position of Baltica remained widely unchanged. This implies that the Moravian Zone lost its former contact to Baltica and that a major Late Variscan fragmentation of the Old Red continental margin must have occurred in the Moravo-Silesian area at that time. Also within the Bohemian Massif, this rotation event may have caused a significant Late Variscan (fault bounded) disturbance of previous terrane relationships. The Bavarian Phase (330-315 Ma) represents a fully independent stage of the Variscan orogeny in the Bohemian Massif. It is defined by a significant reheating (LP-HT regional metamorphism combined with voluminous granitic plutonism) and a tectonic remobilisation of crust in the south-western sector of the Bohemian Massif. These processes were most likely triggered by a Late Variscan delamination of mantle lithosphere. The Bavarian Phase overprinted western parts of the (widely cooled) Moravo-Moldanubian Fold Belt and transformed these rocks into various anatexites (metablastites, metatexites and diatexites). The HP-HT rocks of the Gfohl Unit, the Durbachite plutons, the LP-HT rocks of the Ostrong Unit and other typical constituents of the Moravo-Moldanubian Fold Belt can be followed from the Czech Republic southwards into eastern Bavaria and western Upper Austria (Muhl and Sauwald Zone), but are difficult to identify there due to the strong anatectic overprint. The LP-HT regions further west (Oberpfalz and western Bavarian Forest, Sumava Mts.?) may include former continuations of Tepla-Barrandian or Saxothuringian crust.
Keywords: Bavarian Phase; Moravo-Moldanubian Phase; tectonic model; delamination of mantle lithosphere; monazite dating; Bohemian Massif; Variscan Fold Belt